The Stem Cell Hypothesis of Aging - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2010)
BACKGROUND: There is probably no single way to age. Indeed, so far there is no single accepted explanation or mechanisms of aging (although more than 300 theories have been proposed). There is an overall decline in tissue regenerative potential with age, and the question arises as to whether this is due to the intrinsic aging of stem cells or rather to the impairment of stem cell function in the aged tissue environment.CONTENT: Recent data suggest that we age, in part, because our self-renewing stem cells grow old as a result of heritable intrinsic events, such as DNA damage, as well as extrinsic forces, such as changes in their supporting niches. Mechanisms that suppress the development of cancer, such as senescence and apoptosis, which rely on telomere shortening and the activities of p53 and p16INK4a may also induce an unwanted consequence: a decline in the replicative function of certain stem cells types with advancing age. This decrease regenerative capacity appears to pointing to the stem cell hypothesis of aging.SUMMARY: Recent evidence suggested that we grow old partly because of our stem cells grow old as a result of mechanisms that suppress the development of cancer over a lifetime. We believe that a further, more precise mechanistic understanding of this process will be required before this knowledge can be translated into human anti-aging therapies.KEYWORDS: stem cells, senescence, telomere, DNA damage, epigenetic, aging